Strategic management paper for Mirant Philippine Corporation - Guibelondo, Chuyie Kaye M. (Animo Repository, 2006)
This study is purposely done to formulate strategies for Mirant Philippines Corporation. The study discussed the various regulatory and industry factors that has direct impact on the business landscape of the power industry specifically the power generation sector in which Mirant is a big player. The electric Power Industry Reform Act (EPIRA) was discussed with emphases on Open Access and Retail Competition as well as the Wholesale Electricity Spot Market (WESM). The forecasted in the country was also discussed. A competitor analysis was also done in the study with a feature on the existing and the planned activities of these competitors to penetrate the generation sector market because of the potential of sector to generate additional income. Given the industry landscape, competitor analysis, the study will be discussing the two-component strategy that enable Mirant to protect its generation business, its reputation and for the company to explore growth opportunities. The strategies are anchored on the companys strategic and financial objectives backed-up by the internal capabilities of the company.